WAJAH PANGAN ASIA TIMUR DALAM SELIMUT NEOLIBERALISME STUDI KASUS : CINA - Nur Utaminingsih (UIN ALAUDDIN MAKASSAR, 2019)
The globalizations era, in which every side that involve directly or indirectly always getting encourage even force to build the target, generally, are to be develop country. The 20th century is the era where the actor of international relations was introduced to the new term, some new recipe with the big offers to develop. The recipes that are very influence and became hidden agenda almost happen in every international interactions called neoliberalism. Keywords: Neoliberalism, Food Crisis, Developmentalis